Adaptation to prison and psychopathy - Gonçalves, Rui Abrunhosa (2004)
[Excerpt] Psychopathy is a widely used concept in forensic and correctional settings. Many prison wardens don't hesitate to call their most difficult inmates psychopaths, due to their continuous breaking rules behaviour, their violence and their apparently endless incapability to learn from punishment. Also psychopaths have been described as human predators who take and do what they want to do without any respect, sense of regret or guilt, for others or for social norms (Hare, 1993, 1996). Although these individuals represent only about 196 of the general population and between 15 or 20% of the prison population, nevertheless they are by far the group of offenders who commit more crimes and remain criminally active for the largest periods of time, In Portugal, the diagnosis of psychopathy or antisocial personality disorder is based on DSM or lCD criteria. However, reliance only on diagnostic criteria with-out more objective testing has been controversial (e.g., Hare, 1996; Flare Sc. Hart, 1995: Hare, Hart & Harpur, 1991; Livesley, 1998; Widiger & Corbitt, 1995). The most widely used and cross-culturally valid measure (see Cooke, 1998; Fulero, r995), the Psychopathic Checklist-Revised (Hare, 1994 has not been translated into Portuguese. One objective of the present study was to translate this measure and test it in a sample of prison inmates in Portugal. [...]